2015
DOI: 10.1142/s1758825115500507
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution for Free Vibration of Laminated Curved Beam with Magnetostrictive Layers

Abstract: An analytical model to study the free vibration suppression of laminated curved beam with embedded actuating layers is presented in this study. The magnetostrictive layers are used to control and enhance the vibration suppression. The governing differential equations of the model are derived using the Hamilton principle. Analytical solution of the equations governing laminated curved beam with embedded magnetostrictive layers are obtained for simply-supported boundary conditions. Velocity feedback with constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…For the curved beams restricted asymmetrically, the nonlinear frequency-amplitude curves are drawn in Fig. (3). In the case of fixed-simple supporting, the nonlinear frequencies increase with increasing amplitude for each curves.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For the curved beams restricted asymmetrically, the nonlinear frequency-amplitude curves are drawn in Fig. (3). In the case of fixed-simple supporting, the nonlinear frequencies increase with increasing amplitude for each curves.…”
Section: Figurementioning
confidence: 99%
“…A solid regular polygon cross section has been selected. Bayat et al(2015) studied a laminated curved beam with the embedded magnetostrictive layers under simply-supported boundary conditions. They examined the effects of material properties, radius of the curvature and magnetostrictive layers on the vibration suppression.…”
mentioning
confidence: 99%
“…They found that higher gain control leads to a lower frequency. The analysis of a curved beam with magnetostrictive layers was performed by Bayat et al (2015). They used Terfenol-D as the magnetostrictive material.…”
Section: Introductionmentioning
confidence: 99%
“…After about a decade, Hong 3 presented a new paper dealing with the thermo-mechanical transient dynamic responses of laminated composite plates. The free vibration problem of laminated composite curved beams including magnetostrictive layers was solved by Rahmani et al 4 On the other hand, evidently there is no doubt in the science society on the enhanced specifications of composite materials. As a matter of fact, these improved characteristics are not unbelievable because once two different materials are mixed the achieved material would possess some properties of each of those initial components.…”
Section: Introductionmentioning
confidence: 99%
“…The free vibration problem of laminated composite curved beams including magnetostrictive layers was solved by Rahmani et al. 4…”
Section: Introductionmentioning
confidence: 99%